Elementary School Management Based School perating Cost (A Site at SD Tidar 1 Magelang) - Waluyo, Ign. Slamet (2011)
The objectives of this research are to describe (1) the characteristic of policy of BOS program at SD Tidar 1 Magelang; (2) the characteristic of BOS fund allocation at at SD Tidar 1 Magelang. This research is a qualitative research with ethnography design. This research was conducted in SD Tidar 1 Magelang. The resource persons in this research are the principal, BOS treasurer, and teacher. Data collection method used is in-depth interview, observation, and documentation. Data analysis used is an analysis technique arranged in a site. The validity of data uses triangulation. The results of the research show: (1) The policy of BOS fund includes (1)recording the whole number of students and providing the information and data required by central BOS management team; (b) checking the fund received according to the number of students; (c) appointing the BOS treasurer separated with the routine treasurer; (d) Preparing the School Budget with involving parents. Determining the transparence BOS program policy is a positive way that can be used properly by parents to give their opinion and carry out their role as the control function to the use of fund in the school. There is a cooperation between the principal and parent that show a democratic of policy-making; (2) according to the priority scale if a post is less can be taken to the other post which is still full (egah-eguh system); (b) for procurement of textbook and teaching book, recruiting new student, activity of repairing and maintaining school infrastructure, financing bills, guiding activity and developing professionalism of teacher, enrichment activity and remedial, and developing student's talent and interest. The proper use of fund according to the school's need and the rule set is expected to improve the quality of learning. All school communities and parents have the same obligation to actively supervise the use of BOS fund in order to minimize the misuse of the fund.